The effect of financial liberalization on banking sector stability. Issue 5 (2nd September 2016) - Hamdaoui, Mekki; Zouari, Abir; Maktouf, Samir
Abstract: Several studies indicate that financial liberalization increases likelihood of a financial crisis without distinguishing between a normal period, unstable period preceding the onset of banking panics and crisis/post period. We explain in this paper the relationship between financial liberalization and banking sector vulnerability. Then, we argue that banking sector turmoil is most likely to occur after an intermediate degree of liberalization. Using a recently updated dataset for financial reforms, we find an inverted U-shaped relationship between liberalization and the likelihood of banking crisis for a sample of 49 countries between 1980 and 2010. We used a multinomial logit model in order to take into account what is called the 'post crisis bias'. We ask whether the relationship remains when institutional characteristics of countries and dynamic effects of liberalization are considered. The empirical results indicate that the relationship between liberalization and banking sector stability depends strongly on the strength of capital regulation and supervision. With very weak regulation and supervision, the probability of banking crises is increasing with liberalization but this relationship is reversed as regulation and supervision become significant. The most important type of liberalization in relation to banking crises seems to be operational. A policy implication is that positive growth effects of liberalization can be achieved without increasing the risk of a banking fragility if appropriate institutions are developed.